Girls trip [videorecording (DVD)] - Hall, Regina; Haddish, Tiffany, 1979-; Tate, Larenz; Walsh, Kate, 1967-; Smith, Jada Pinkett, 1971-; Queen Latifah, 1970- (Universal Pictures Home Entertainment, 2017)
When four lifelong friends travel to New Orleans for the annual Essence Festival, sisterhoods are rekindled, wild sides are rediscovered, and there's enough dancing, drinking, brawling and romancing to make the Big Easy blush.